PERSEPSI ANGGOTA TERHADAP PERAN DAN TUJUAN KELOMPOK TANI DALAM PENERAPAN SISTEM INTEGRASI SAPI-JAGUNG DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Fani Agustiana Wati; Susy Edwina; Jumatri Yusri (Fakultas Pertanian, Universitas Riau, 2022)
System Integration is an activity that combines two or more efforts with the aim of increasing profits. The application of the Crop Livestock System is an effort to combine corn and cattle crops in the farmer's farming system. The purpose of the study was to determine the perception of members towards the role of farmer groups (as learning classes, production units and cooperation vehicles) in the application of the integration system, to find out members' perceptions of the implementation of institutional aspects and the objectives of farming groups. There were 17 respondents who were members of the Prima Jaya farming group. The research was conducted in Marpoyan Damai District, Pekanbaru City, October 2018 to April 2019. The research method is a survey with a sampling technique carried out by purposive sampling. The data analysis techniques used are validity tests, reliability tests using SPSS 17.0, descriptive analysis and likert scales. The results showed: Members' perceptions in general of the role of farming groups in the implementation of the integration system are in the good category, farmers' perceptions of institutional aspects are in the excellent category, the goals of farmer groups are in the good category, which shows that better farming, better business and better living have been achieved.